Structure–function insights reveal the human ribosome as a cancer target for antibiotics - Alexander G. Myasnikov (Nature Portfolio, 2016)
The ribosome of bacteria and other unicellular pathogens is a common target for antibiotic drugs. Here the authors determine a structure of the human ribosome bound to the translation inhibitor cycloheximide, and provide evidence that targeting the ribosome is a promising avenue for cancer therapy.